Impact of community engagement on public acceptance towards waste-to-energy incineration projects: Empirical evidence from China. (June 2018) - Liu, Yong; Sun, Chenjunyan; Xia, Bo; Cui, Caiyun; Coffey, Vaughan
Highlights: How community engagement affects public acceptance towards WTE projects is studied. Public acceptance is affected by demographic variables. Public trust positively affects public acceptance both directly and indirectly. Community engagement can effectively enhance public trust in WTE authorities. Abstract: As one of the most popular methods for the treatment of municipal solid waste (MSW), waste-to-energy (WTE) incineration offers effective solutions to deal with the MSW surge and globe energy issues. Nevertheless, the construction of WTE facilities faces considerable and strong opposition from local communities due to the perceived potential risks. The present study aims to understand whether, and how, community engagement improves local residents' public acceptance towards waste-to-energy (WTE) incineration facilities using a questionnaire survey conducted with nearby residents of two selected WTE incineration plants located in Zhejiang province, China. The results of data analysis using Structural Equation Modeling (SEM) reveal that firstly, a lower level of public acceptance exists among local residents of over the age of 35, of lower education levels, living within 3 km from the WTE Plant and from WTE incineration Plants which are under construction. Secondly, the public trust of local government and other authorities was positively associated with the public acceptance of the WTE incineration project, both directly and indirectly based on perceived risk. Thirdly, community engagement can effectively enhance public trust in local government and other authorities related to the WTE incineration project. The findings contribute to the literature on MSW treatment policy-making and potentially hazardous facility siting, by exploring the determinants of public acceptance towards WTE incineration projects.